KOMODIFIKASI TUBUH PEREMPUAN (ANALISIS WACANA KRITIS PADA AKUN TIKTOK VIRTUAL INFLUENCER @LENTARI.PAGI) - Emy Rahma Putri; Mustika Chairil, Augustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The emergence of virtual influencers presents a new form of female representation on social media because the bodies displayed are not biological, but are digitally produced and controlled. This study aimed to analyze the commodification of the virtual female body on the TikTok account @lentari.pagi through content commodification, audience commodification, and indications of economic value within the platform ecosystem. The study employed a qualitative approach with a critical paradigm. The research data consisted of eight TikTok posts selected through criterion-based purposive sampling, including videos, visual elements, captions, interaction metrics, and audience comments. The data were analyzed using Sara Mills's critical discourse analysis to examine the positions of the subject, object, and reader, and were subsequently linked to Vincent Mosco's theory of commodification. The results showed that Riri was constructed as a pseudo-subject who built intimacy through a digital persona and personal narratives, while her body was simultaneously positioned as a visual object that was displayed, judged, sexualized, and objectified. Content commodification occurred through the packaging of the virtual body as a flexible visual attraction for promotional content, entertainment, and popular issues. Audience commodification occurred when views, likes, comments, and shares became forms of digital labor that increased engagement and account visibility. The study concluded that the virtual female body on @lentari.pagi functioned as an attention commodity, in which the digital body generated attention, attention produced engagement, and engagement opened opportunities for potential commercial value.